Procedure for the structural synthesis of the logistic support system to the air force grouping of the armed forces of Ukraine in preparation for combat operations - Gurin, Alexander; Musienko, Oleksandr; Khomik, Mykola; Vavilova, Nadiia; Hurin, Ihor (Eastern-European Journal of Enterprise Technologies, 2023)
This paper considers elements of the methodology for the structural synthesis of the logistic support system of the Air Force grouping of the Armed Forces of Ukraine during the preparation for combat operations. Contradictions between the growing need for military units in material and technical means and the limited capabilities of the existing system of logistical support of the troop group predetermined the relevance and practical focus of this study. Measures have been devised that affect the logistical support of the troop group. It is proposed to implement a mixed centralized-decentralized principle of building a logistics support system based on «material support clusters», which could ensure timely and complete delivery of material and technical means. During the research, it was established that reducing the response time to changes in the volume of supplies of material and technical means in military units would ensure the continuity of the operation of weapons and military equipment, and this would give signs of the adaptability of the proposed logistics support system. It is theoretically justified that the use of the proposed methodology could affect the actual availability of established military reserves of the troop group and obstacles that prevent timely replenishment of daily expenses and losses. The remoteness of military units and separate units from provision agencies and the limited means of transporting material and technical means were taken into account. The calculations of the efficiency assessment of the developed structure of the logistic support system allow us to draw conclusions about its superiority over the existing one by 14–17 % by ensuring the continuity of combat operations. The idea and elements of the devised methodology could be used in the calculations of transport tasks of civil enterprises